Health Centers in States With Public Health Agency Support Do Not Have Better Chronic Disease Outcomes - Brad Wright; Andrew J. Nice (SAGE Publishing, 2014)
Objectives: To examine the quality of chronic disease care at federally qualified health centers (FQHCs) as a function of state health agency support. Methods: We merged data from the 2010 Association of State and Territorial Health Officials Public Health Survey, the 2011 Area Resource File, and the 2010 Uniform Data System. Using ordinary least squares regression, we modeled hypertension and diabetes control among FQHC patients as a function of state public health agency support of FQHCs, including financial support, direct collaboration, and electronic health data exchanges. Results: The rate of hypertension control is 63.4%, while the rate of diabetes control (HbA1c <7%) is 41.3%. Some two thirds of FQHCs (67.1%) are in states whose public health agencies are fully engaged in FQHC-supporting activities, and approximately one third (34.6%) are in states whose public health agencies send and receive electronic health record data with FQHCs. However, none of our measures of public health agency support of FQHCs significantly predicted FQHC-specific chronic disease outcomes. Conclusions: We find no evidence that state public health agency support of FQHCs affects chronic disease outcomes for FQHC patients.